Análise da identidade social de jovens egressos após participação no Programa de Formação da AESP - Pereira, Carlos Eduardo (2016)
The purpose of this research is to identify and analyze their lives of young people who participated in a training program of AESP - Social Education Association, more specifically in six areas: how is your relationship with family, friends, the school/college, in solving problems in their choices in the professional, what they think about challenges and opportunities for the future and how was the participation in the program. The idea was to start work by proposing a discussion of all that they have made in their lives, they do good, useful or superfluous. This research proposed to the young participants know what are the perceptions of their role in society, their share of contribution and responsibility for solving problems. The proposed issues were discussed in a clear and objective manner. Within the analysis it was possible to visualize a set of possibilities able to transform the lives of these young people, their families and to the community to which they belong. It is during youth, especially in high school, young people have a single goal: the choice of a profession. The construction of the youth's social identity is planting seeds in fertile ground in order to have a good harvest. In this way we must then stop and think about what you have done to be better, to be different. The main question of this work focused on the question: In what turned out to have participated in the training program of the AESP? Was there changes regarding behaviors, knowledge and emotions? Does this young man could choose their profession? Are you working? Are you working in the area you want to act? What has been done by these young people to achieve, maintain, and even reinforce a positive self-image of citizen and professional? The collection of information search techniques were the focus group and semi-structured individual interviews, organized in themes related to personal and family data of young people, such as friends, studies, participation in the training program, future challenges and employment. Individual interviews contributed to the understanding of certain reports. In summary, in the senses expressed between "loss" and "gain", there is a positive prevalence in their views and shared experiences. It was possible to see that these young people have learned and, and that the search for more professional opportunity to carry out doing what you like, bring wishes in seeking to be someone, to be happy from a new cycle of their lives